High-resolution surface mass loads in the Amazon Basin combining GRACE and river routing model. Issue 3 (9th November 2022) - Youm, Kookhyoun; Eom, Jooyoung; Seo, Ki-Weon; Chen, Jianli; Wilson, Clark R; Oh, Seokhoon
SUMMARY: Understanding water redistribution on Earth's surface is essential to hydrological applications and water management. Variations in water mass loads have been observed by the Gravity Recovery and Climate Experiment (GRACE), but the low spatial resolution of GRACE limits determination of their distribution in detail. Hydrologic models provide higher spatial resolution water mass loads, but may include larger uncertainties. In this study, we develop high-resolution surface mass loads over the Amazon basin using forward modelling by combining GRACE data and a hydrologic model. River routing discharge is also included as a priori information because of the large water volume changes on relatively narrow channels in the Amazon basin. These high-resolution surface mass loads constrained by river routing agree with GRACE observations when spatially smoothed. Vertical deformation estimated from these high-resolution loads agree with Global Navigation Satellite System (GNSS) observations, at both seasonal and inter-annual timescales. In particular the most improved agreement is obtained at the NAUS GNSS station, close to the main channel of the Amazon, relative to predictions made using GRACE data. At two other stations (APSA and MAPA) near the main channel, the estimated vertical deformations apparently differ from observation, but much of the discrepancy is reduced when river path is corrected in river-routing model, indicating the importance of water loads on river channel to understand crustal displacement in the area.